ANALYSIS EFFECT OF MUDHARABAH FINANCING SHARING ON PROFITABILITY AT BRI SYARI'AH KCP CIAMIS 2014-2020 - Helmi Maulana; Dedeh Nurwahidah; Willa Maulida (Syari'ah Economics, 2021)
As an institution engaged in the financial sector, Islamic banks expect benefits from the activities that have been carried out. This profit is generated through income generated from the products that are distributed. The performance of banks in carrying out their activities is seen from how much financing is distributed because the source of income for Islamic banks is from financing distribution. The volume of financing provided by Islamic banking needs to show an increase in order to create healthy and efficient financial institutions. Healthy financial institutions are able to demonstrate the ability to increase profits through increased profitability. The higher the profitability of a bank, the better profits or profits will be generated by the bank. Return on Assets (ROA) is one of the financial ratios in banking which has the best role to reflect the level of profitability of the bank. This research method uses quantitative descriptive method where quantitative descriptive method is a method in examining the status of a human group, an object, a set of conditions, a system of thought, or even a group of events in the present which aims to make a description. This research uses simple regression analysis which includes partial test (t test), and coefficient of determination test (R2). From the partial test (t test) obtained t count of 10.027 > from the value of t table of 2.228139. It is known that the p-value < (0.000 < 0.05) indicates that the multi-finance variable has a significant effect on Return On Assets (ROA). Coefficient of Determination Test (R2) regression model, the adjusted R2 value is 0.900, which means that the dependent variable can be explained by the independent variable by 90%, while the remaining 10% is explained by other variables not included in the regression model. The results of the partial test (t-test) and the coefficient of determination (R2) show that murabahah financing has a significant effect on the Return on Assets (ROA) profitability ratio at BRI Syariah KCP Ciamis Bank for the 2018-2020 period.